MARKETING STRATEGY TO INCREASE TOURIST VISITS ON NATURE TOURISM OF MEMPAWAH MANGROVE PARK IN THE PASIR VILLAGE OF MEMPAWAH REGENCY - Utin Nina Hermina (STKIP Singkawang, 2019)
Nature tourism is one of the tourism that is trending and loved both local and foreign tourists. It is expected to bring an impact on improving the region's economy, and the community around the tourist attractions can be actively involved in there. Mempawah Regency is one of the regencies in West Kalimantan, one of its natural attractions is